Impact of Social Franchising on Contraceptive Use When Complemented by Vouchers: A Quasi-Experimental Study in Rural Pakistan - Khurram Azmat, Syed (Public Library of Science, 2013)
BACKGROUND: Pakistan has had a low contraceptive prevalence rate for the last two decades; with preference for natural birth spacing methods and condoms. Family planning services offered by the public sector have never fulfilled the demand for contraception, particularly in rural areas. In the private sector, cost is a major constraint. In 2008, Marie Stopes Society – a local NGO started a social franchise programme along with a free voucher scheme to promote uptake of IUCDs amongst the poor. This paper evaluates the effectiveness of this approach, which is designed to increase modern long term contraceptive awareness and use in rural areas of Pakistan. METHODOLOGY: We used a quasi-experimental study design with controls, selecting one intervention district and one control district from the Sindh and Punjab provinces. In each district, we chose a total of four service providers. A baseline survey was carried out among 4,992 married women of reproductive age (MWRA) in February 2009. Eighteen months after the start of intervention, an independent endline survey was conducted among 4,003 women. We used multilevel logistic regression for analysis using Stata 11. RESULTS: Social franchising used alongside free vouchers for long term contraceptive choices significantly increased the awareness of modern contraception. Awareness increased by 5% in the intervention district. Similarly, the ever use of modern contraceptive increased by 28.5%, and the overall contraceptive prevalence rate increased by 19.6%. A significant change (11.1%) was recorded in the uptake of IUCDs, which were being promoted with vouchers. CONCLUSION: Family planning franchise model promotes awareness and uptake of contraceptives. Moreover, supplemented with vouchers, it may enhance the use of IUCDs, which have a significant cost attached. Our research also supports a multi-pronged approach- generating demand through counselling, overcoming financial constraints by offering vouchers, training, accreditation and branding of the service providers, and ensuring uninterrupted contraceptive supplies.